Smarter Travel, car restriction and reticence: Understanding the process in Ireland's active travel towns. Issue 2 (June 2017) - Lambe, Barry; Murphy, Niamh; Bauman, Adrian
Highlights: Car restrictive policies are underused and undervalued in Ireland. Retail traders equate car accessibility with retail turnover. Retail traders influence the nature and pace of active travel policy implementation. Making the business case for introducing car restrictive policies is essential. Community advocates for active travel need to be mobilised. Abstract: The purpose of this qualitative study was to examine the factors that precluded the introduction of car restrictive policies in two towns participating in Ireland's Smarter Travel programme to promote sustainable travel. A total of 14 semi-structured interviews were conducted with the project co-ordinators, community advocates for active travel and retail traders (shops and small businesses). The results indicated that the Smarter Travel co-ordinators were inexperienced in using a full range of pricing, programming and policy measures specific to active travel. A more significant factor was the power of the trader lobby. In the town with the lower population density, car accessibility in the urban centre was perceived by retail traders to be directly associated with retail turnover. In the town with the higher population density, retail traders stated that car accessibility created an illusion of vibrancy that provided security to the retail sector. The retail traders disliked the local authority's didactic approach to consultation and this dissonance manifested itself in displays of power against the local authority and not necessarily against Smarter Travel per se. Both local authorities struggled to sell the business case for car restrictive policies to the retail traders. They also failed to engage the silent majority in the wider community to act as advocates for active travel. The wider implications for the implementation of Smarter Travel policy are presented. It is important to create community support for active travel interventions by forming 'town user' forums and active travel lobby groups and making the local media partners in the project. Training and support should be provided to local authorities to deliver a more comprehensive suite of measures. A toolkit should be developed for local authorities to create a business case for introducing car restrictive measures. Incentives such as improvements to the public realm and accessibility for cyclists should be introduced before car restrictive measures. Car restrictive measures should be introduced incrementally such as introducing temporary pedestrianization or gradually reducing parking supply thereby demonstrating the benefits of the measure to stakeholders.